2017
DOI: 10.1073/pnas.1618856114
|View full text |Cite
|
Sign up to set email alerts
|

ERAP1 association with ankylosing spondylitis is attributable to common genotypes rather than rare haplotype combinations

Abstract: We investigated the proposal that ankylosing spondylitis (AS) is associated with unusual ERAP1 genotypes. ERAP1 haplotypes were constructed for 213 AS cases and 46 rheumatoid arthritis controls using family data. Haplotypes were generated from five common ERAP1 single nucleotide polymorphisms (SNPs)—rs2287987 (M349V), rs30187 (K528R), rs10050860 (D575N), rs17482078 (R725Q), and rs27044 (Q730E). Haplotype frequencies were compared using Fisher’s exact test. ERAP1 haplotypes imputed from the International Geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 21 publications
2
31
0
1
Order By: Relevance
“…Hap1/Hap2 are risk haplotypes for AS and psoriasis [8,12], while being protective for BD and Birdshot. Therefore, Hap10 and Hap2 of ERAP1 play a central role for patients within the MHC-I-opathy cluster: patients with psoriasis have an increased risk of uveitis [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hap1/Hap2 are risk haplotypes for AS and psoriasis [8,12], while being protective for BD and Birdshot. Therefore, Hap10 and Hap2 of ERAP1 play a central role for patients within the MHC-I-opathy cluster: patients with psoriasis have an increased risk of uveitis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 10 | Non-random distribution of the ERAP2-protein coding haplotype across common ERAP1 haplotypes based on 5 SNPs. Five missense variants in ERAP1 encode four discrete and common (>1% freq) haplotypes [12], while ERAP2 encodes 1 common protein-coding haplotype (HapA tagged by the A allele of rs2248374) and non-coding haplotypes (tagged by the G allele). Each chromosome harbors 1 ERAP1 haplotype and 1 ERAP2 haplotype.…”
Section: Supplementary Figure 8 | the Common Splice Region Variant Ofmentioning
confidence: 99%
“…Several studies agree to indicate the high trimming Met349/Lys528/Asp575/Arg725/Gln730 haplotype as being associated most strongly with AS risk, while the low trimming Val349/Arg528/Asn575/Gln725/Glu730 haplotype as the most protective [2,78,88]. In contrast, a report has suggested that rare hyperactive or hypoactive allotype pair combinations found in AS patients could explain the involvement of ERAP1 in the disease [79].…”
Section: Hla-b27 and Erap1/2 As Players In Ankylosing Spondylitismentioning
confidence: 98%
“…A recent study investigated haplotypes generated from five common ERAP1 SNPs—rs2287987 (M349V), rs30187 (K528R), rs10050860 (D575N), rs17482078 (R725Q) and rs27044 (Q730E), and further confirmed that the association of ERAP1 with AS is primarily contributed by individual common ERAP1 genotypes, rather than by haplotypes. 62 …”
Section: Aminopeptidase In Asmentioning
confidence: 99%